(untitled) (Kampelmas, 2022)
This paper aims to improve the quality of public health through the provision of SPAL (Wastewater Sewerage) in Karangcengis Village, Bukateja, Purbalingga. This service method is carried out by means of observation based on community empowerment. From observations made to obtain the fact that there are still people who pay less attention to environmental hygiene, one of them is by not disposing of waste water in its place. The result of this service is to build SPAL in ten different locations as an effort to improve the health of the people of Karagcengis Village. The construction of SPAL at several points is also expected to be an example for other communities to participate in building SPAL in their homes.